DEVELOPMENT OF ANTITAXIAL STRAIN FRINGES DURING NON-COAXIAL DEFORMATION: AN EXPERIMENTAL STUDY - Koehn D.; Bons P.D.; Passchier C.W. (My University, 2003)
Strain fringes were modelled experimentally around wooden objects in a simple-shear box containing Polydimethylsiloxane (PDMS). The fringes were made of paraffin wax that was periodically poured into dilated sites next to the core-object and left to crystallise. In the experiments fringes and core-object rotated at similar decreasing rotation rates relative to extensional incremental stretching axes (ISA) of flow and rotated relative to each other by small amounts. Fringes did not necessarily open parallel to ISA due to interactions between fringes and core-object. Therefore, neither displacement-controlled fibres nor object-centre paths can be expected to record the exact orientation of the extensional ISA, but only give estimates. Existing methods to calculate finite strain were applied to the experimental fringes. These methods generally underestimate the actual finite shear-strain. This study illustrates that different final fringe shapes can develop in the same shear zone depending on core-object shape and its initial orientation with respect to the shear zone boundary. A classification of final fringe shapes is presented based on the initial orientation of elongate core-objects.
Keywords: STRAIN FRINGES; STRAIN ANALYSIS; FIBRES; ROTATION; TRANSLATION